Toward a theory of entrepreneurial rents: A simulation of the market process. (2nd January 2014) - Keyhani, Mohammad; Lévesque, Moren; Madhok, Anoop
<x xml:space="preserve">Abstract</x> While strategy theory relies heavily on equilibrium theories of economic rents such as Ricardian and monopoly rents, we do not yet have a comprehensive theory of disequilibrium or entrepreneurial rents. We use cooperative game theory to structure computer simulations of the market process in which acts of creation and discovery disequilibrate and equilibrate the market over time. Using simulation experiments, entrepreneurial rents can be isolated from structural rents by keeping initial structural advantages constant. We impute entrepreneurial rents to underlying actions of creation and discovery under various combinations. Our results have relevant implications for entrepreneurship strategy, particularly for firm boundaries and resource allocation decisions. Copyright © 2013 John Wiley & Sons, Ltd.